Pengaruh Pertumbuhan dan Produksi Tanaman Mentimun (Cucumis sativus l.) Terhadap Pemberian Pupuk NPK - Hulu, Arahman; Harahap, Rahmania; Miyarnis, Miyarnis (JURNAL AGROPLASMA, 2024)
Cucumber fruit (Cucumis sativus L) is a plant grown in Indonesia with antioxidant capacity. Preliminary test (phytochemistry) on cucumber fruit showed several active compounds including alkaloids, phenolic compounds, flavonoids, steroids, terpenoids, and saponins. Cucumber fruits are rich in water, low in calories, a source of vitamin C, and contain flavonoids that have antioxidant effects. contain flavonoids that have antioxidant effects by breaking down new radicals. new radicals. Cucumber is included in the group of fruits that can be consumed to lower blood pressure because it has hypotensive properties. lower blood pressure because it has hypotensive properties. The high consumption of cucumber consumption is still not matched by    production and productivity. Hal Therefore, efforts are needed to meet the needs of cucumber production, namely by increasing soil productivity, using the addition of NPK fertilizers. using the addition of NPK fertilizer. This study used a randomized group design group (RAK) factorial. For accuracy in this study it was repeated namely: NPK fertilizer (N) with 3 levels, namely: N0 = Control, N1 = 30 g/plant, and N2 = 60 g/plant. The results of the Anova Variance test showed that the effect of NPK fertilizer treatment on plant height 2 mst, 3 mst, and 4 mst and weight of fruit (g), and number of fruits (g), and the number of fruits did not significant effect, but the observation of fruit diameter (mm) had a significant effect.real effect.  Keywords: NPK fertilizer, NPK dosage,  cucumber plants